573. DOES CHEST PAIN AFFECT THE LONG TERM OTCOME OF SURGERY FOR ESOPHAGEAL ACHALASIA?. (24th September 2022) - Tassi, Valentina; Baldi, Fabio; Lugaresi, Marialuisa; Daddi, Niccolò; Bassi, Francesco; Pilotti, Vladimiro; Mattioli, Sandro
Abstract: Literature supporting the adoption of POEM in place of the standard Heller myotomy in the presence of significant chest pain associated with typical symptoms like in case of Achalasia Type III according to the Chicago classification, generally reports on outcome data collected after short follow up periods. We aimed to assess behaviors of chest pain in the long term in a case series of patients submitted to the Heller-Dor operation. Between 1978 and 2021, 394 achalasia patients underwent the Heller-Dor operation. Chest pain was evaluated according to its frequency (0: absent; 1: occasional; 2: weekly; 3: daily): 81 preoperatively complained of chest pain (score 2-3) (CP group), 313 did not (score 0-1) (NCP group). Patients were followed up according to a timed protocol based on clinical assessment of dysphagia (D0 absent – D3 each meal), GERD symptoms (RS0 absent-RS3 each meal). Barium swallow and endoscopy (E0: normal, E1: mild esophagitis, E2-3: erosive/ulcerative esophagitis) were performed at each planned control. CP and NCP were compared. CP group had shorter duration of dysphagia (p=0.03), smaller esophageal diameter and lower barium column (p<0.05). At a median follow-up of 10 years for CP and 11 years for NCP (p=0.166), the frequency of dysphagia (p=0.05), GERD symptoms (p=0.3) and esophagitis (p=0.27) was similar in the two groups. Chest pain progressively attenuated in intensity and frequency.; median chest pain score preoperatively was 3, at follow-up it was 0 (p<0.01). Clinical results obtained in CP patients (satisfactory D0–2, RS0–2, and E1 in 95%) were not inferior to those obtained in NCP patients (satisfactory in 93%) (p=0.05). According to our single center case series, in the long term chest pain does not influence negatively HD outcome which is absolutely competitive with that generally reported for POEM and pneumatic dilation. Results presented in this study must be verified: as new randomized prospective studies would require a too long lag time, valid retrospective multi center studies should be performed.